Interest-free monetary policy and its impact on inflation and unemployment rates - Mohammad Selim; M. Kabir Hassan (ISRA International Journal of Islamic Finance, 2019)
Purpose: This paper aims to examine the effects of interest-free and interest-based monetary policy on inflation and unemployment rates for two groups of countries where in one group, interest-free monetary policy (IFMP) was pursued, while in the other group, interest-based monetary policy (IBMP) was followed. Design/methodology/approach - This study involves a sample of 23 developed countries divided into two groups. The authors measure economic performance by misery index (MI), and MI is calculated as unemployment rate plus inflation rate. A group of countries, where MI is lower, performs better compared to the other group where MI is relatively higher. Findings - The results reveal that in group of 12 countries where IFMP is adopted, the MI is lower and thus performs better compared to a group of countries where IBMP is pursued. Research limitations/implications - The findings of this study have profound implications for the policymakers and government leaders who look for a solution to maintain both low inflation and unemployment rates. The findings in this study clearly portray that such ideal situations can only be achieved by pursuing IFMP. No wonder the countries which have been historically pursuing IFMP such as Japan, Switzerland, Sweden, the Netherlands and Denmark have been able to contain both inflation and unemployment rates compared to their counterparts among the English-speaking countries. Originality/value - This is one of the most recent tests on the differences in economic performance between IFMP and IBMP. These results have significant value for policymakers and central bankers who have been struggling to maintain lower MI for decades.
Keywords: 330; Economic performance; Interest-based monetary policy; Interest-free monetary policy; Misery index; Qarḍal-Hasan